2013
DOI: 10.3409/fb61_3-4.199
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environmental Factors on Sister Chromatid Exchange Incidence in Domestic Horse (Equus caballus) Chromosomes

Abstract: The SCE test is often used as a sensitive and reliable technique in the biomonitoring of genotoxicity of mutagenic and carcinogenic agents. This study analysed the frequency of sister chromatid exchange in domestic horse chromosomes depending on the habitat and age of the analysed horses. The chromosome preparations were obtained from an in vitro culture of peripheral blood lymphocytes stained using the FPG technique. Both the habitat and the age significantly influence SCE frequency. A higher SCE incidence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Few publications contain reports about statistically significant differences in SCE incidence between males and females (Margolin and Shelby 1985;Husum et al 2008;Szeleszczuk et al 2014). Comprehensive studies of farm animals have not confirmed the effect of the sex on SCE frequency (Iannuzzi et al 1991b;Di Meo et al 1993, 2000Ciotola et al 2005;Peretti et al 2006;Wo´jcik et al 2011Wo´jcik et al , 2013Wo´jcik et al , 2014Wo´jcik and Smalec 2012a). The present authors also did not observe significant differences in the mean number of SCEs between chinchillas of different sexes.…”
Section: Discussionsupporting
confidence: 44%
“…The distinctive secondary narrowing of one of the arms of the X sex chromosome has been described by Kuchta et al (2008), who stressed that this site is often vulnerable to breakage and dissociation in untoward conditions. Proximal SCEs have also been observed in the Chinese hamster (Martin and Prescott 1964), rat (Gibson and Prescott 1972), goat (Wojcik and Smalec 2012a), goose (Wo´jcik and Smalec 2012b), and chicken (Wo´jcik et al 2012). On the other hand, Latt (1974), in man, Iannuzzi et al (1991b), in cattle, and Arias (2000), in chickens, observed SCEs chiefly in the G-positive bands and negative interbands.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…For a more complete assessment of somatic mutagenesis of mesenchymal stem cells, a micronucleus test was performed. The formation of cells with micronuclei is the result of chromosomal ruptures or defects in the mitotic spindle, which is consistent with the manifestation of aneuploidy (15,18,19,(22)(23). The normal frequency of cells with micronuclei in mammals is 1.6‰-5.6‰ (8).…”
Section: Discussionmentioning
confidence: 70%